Switching from linear to macrocyclic gadolinium‐based contrast agents halts the relative T1‐Weighted signal increase in deep gray matter of children with brain tumors: A retrospective study. Issue 1 (4th June 2019) - Rowe, Selene K.; Rodriguez, Daniel; Cohen, Ellie; Grundy, Richard; Morgan, Paul S.; Jaspan, Tim; Dineen, Robert A.
Abstract : Background: Studies have shown signal intensity (SI) changes in the brains of children exposed to repeated doses of a gadolinium‐based contrast agent (GBCA). Hypothesis: The trajectory of changes in relative dentate nucleus (DN) and globus pallidus (GP) SI in children receiving multiple doses of GBCA will alter when switched from linear to macrocyclic agents. Study Type: Retrospective longitudinal. Population: Thirty‐five children, age range 0.5–17.0 years, undergoing brain tumor follow‐up between 2006 and 2017. Field Strength/Sequence: Unenhanced T1 WI, serial scans at both 1.5T and 3T. Assessment: Regions of interest were drawn on DN, GP, and SIs normalized to middle cerebellar peduncle (DN/MCP) and cerebral white matter (GP/CWM), respectively. A change in SI ratios as a function of dose (slope gradient) calculated according to the type of contrast agent received: linear only, macrocyclic only, or switchover from linear to macrocyclic. For the latter, gradients were compared before and after switchover. The effect of anticancer treatment on slope gradient was tested. Statistical Tests: One‐sample t ‐test or Mann–Whitney U ‐test for slope gradients differing from zero. Independent samples t ‐tests to compare slope gradient groups. Paired sample t ‐tests to compare slope gradients before and after switchover. Results: A significant ( P < 0.05) increase in SI ratio was observed following multiple doses of linear but not macrocyclic agents: mean percentage increase per dose in SI was 0.063% vs. –0.034% for DN/MCP, and 0.078% vs. 0.004% for GP/CWM ratios. A significant ( P < 0.05) change of SI trajectory in the DN/MCP ratio was demonstrated when switching from a linear to macrocyclic agent. There was no difference in SI trajectory between patients who had anticancer therapies and those who did not, DN/MCP P = 0.740; GP/BWM P = 0.694. Data Conclusion: Switching from linear to macrocyclic gadolinium‐based contrast agents seems to halt the relative T1 signal increase in deep gray matter in children. Anticancer treatments appeared to have no impact on the trajectory of T1 SI. Level of Evidence: 4 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2020;51:288–295.